Corporate social responsibility and its effect on community development: an overview - Masum, Ahmad; Abdul Aziz, Hajah Hanan Haji Awang; Ahmad, Muhamad Hassan (International Organization of Scientific Research, 2020)
Traditionally, businesses primarily exist to make profit. The profit motive has often been perceived as representing a lack of concern for all other objectives of an organisation. But, today businesses are realising that in order to stay profitable in a rapidly changing environment, they would have to become socially responsible. Hence, there is a growing demand and expectation from various stakeholders who expect business to go beyond their profit agenda and be socially responsible. The belief that beyond making profit for the shareholders, business enterprises should also serve the interest of all other stakeholders has culminated into the concept of Corporate Social Responsibility (CSR). This concept has engendered considerable interest in recent years. CSR refers to strategies corporations or firms conduct their business in a way that it’s ethical, society friendly and beneficial to the community development. The objective of this paper is to examine the effect of CSR on community development. The paper adopts a library based research methodology focusing mainly on primary and secondary sources. The result of this paper shows that the traditional view of business being essentially to maximise profit has changed in recent years. The traditional view is no longer accepted in today’s business environment. Corporations have now adopted the concept of CSR, which is concerned with economic, environment, and social performance. The paper concludes that the effect of CSR on community development can be seen from different angles like protecting the environment. Some of the world’s largest companies have made a highly visible commitment to CSR, for example, with initiatives aimed at reducing their environmental footprint.